Creation and Metaphysics - Thibault, Herve J. author. aut Link
XII, 87 p.
Keywords: During the last twenty-five years or so, studies in Thomistic existentialism have repeatedly indicated that the notion of creation played a decisive role in St. Thomas Aquinas' view of existence as an existential act or actus es sendi. The importance for metaphysics of this view of existence as act war rants an investigation of the relation between creation and actus essendi; for St. Thomas is the only one, in the history of philosophy, to have con sidered existence as an act-of-being. This study will be limited to the early works of St. Thomas. By the time of the Summa Contra Gentiles, he had reached the key positions of his metaphysics. And the first fifty-three chap ters of the Summa Contra Gentiles were written in Paris before June, 1259; 1 the rest was completed in Italy before 1265. The project was therefore con ceived by St. Thomas during the first period of his career. How the notion of creation enabled him to transform the Aristotelian metaphysics of essence into a metaphysics of esse can be seen from three sections of the Summa Contra Gentiles. Although primarily a theological treatise, the Contra Gentiles never theless accomplishes a radical metaphysical transformation of Aristotelian ism by shifting the whole perspective from esse in actu per formam to actus essendi. Seen from the perspective of existential act as the absolute perfec tion, metaphysics is raised to a strictly transcendental plane of consideration.